Qualidade de vida no trabalho do profissional de saúde que atua em sala de aula de trauma. Estudo de caso: serviço de emergência do Hospital Universitário Antônio Pedro - Niterói. - Escudeiro, Andreia Pereira (2003)
This paper was developed in the Emergency Room of University Hospital Antônio Pedro, in Niterói, Rio de Janeiro, based on the author s personal observation about the ergonomic risks. It presents a study on perception about the quaiity of life in the work, among the health workers. Applying the methodology of Work Ergonomics Analysis, it aims to identify the ergonomic hazards that affect lhe quality of life ín the work. Among them, the principal factors are the inadequate luminance, the height and disposition of the working tabies and the stressing factors. Based on that analysis recommendations were made in order to correci the ergonomic risks and to make better the quality of life in the work in that Room. lt was conciuded that the present ergonomic risks can be corrected by means of minimai adaptative measures, which couid facilitate a better adequacy of the task done at the Emergency Room to the quality of life of the health workers in that place.